Embodiment and there construction of gender roles in Leow Puay Tin's family - Philip, S. (SAGE Publications (UK and US), 2010)
Through an analysis of both the text and performance of Malaysian playwright Leow Puay Tin's Family, this paper looks at the construction of the family unit in a particular segment of Malaysian society, in order to examine the tension existing between socially and authoritatively imposed gender identities and individuals' responses to these imposed identities. Individuals within Leow's fictional family are embodied in specific ways which support and perpetuate patriarchal structures. However, this embodiment is revealed to be groundless and they are therefore forced to reconstitute imposed identities by imagining or living within their bodies differently. The analysis of these issues is enhanced through a study of the production of this play in Kuala Lumpur in 1998, which re-articulated Leow's vision through unusual and confrontational staging, casting and costuming choices which were able to go further than the text in examining and physicalizing questions about the borders and limits of gender identity.